2015
DOI: 10.1016/j.acalib.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

NICE Evidence Search: Student Peers' Views on their Involvement as Trainers in Peer-based Information Literacy Training

Abstract: This research seeks to contribute to understanding of peer-based models of information literacy training, through gathering insights from peer trainers (champions) in a scheme designed to promote the use of a national health and social care information portal, Evidence Search (ES), amongst university students in mainly in the health professions. Specifically, this article focuses on the benefits and learning that the peer trainers derive from their involvement in the scheme. This article reports on focus group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 30 publications
5
11
0
Order By: Relevance
“…The student learners have also expressed the view that ES is not only significantly useful for their course of study, but the relevance of the resource keeps growing with time, possibly due to the increased users’ familiarity with it (Garcia‐Marques, Prada & Mackie, ). This is in agreement with preliminary studies conducted on the impact of NICE Evidence search (Rowley et al., ; Sbaffi et al., ). This finding is also supported by the responses provided regarding the main reasons for using NICE ES.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The student learners have also expressed the view that ES is not only significantly useful for their course of study, but the relevance of the resource keeps growing with time, possibly due to the increased users’ familiarity with it (Garcia‐Marques, Prada & Mackie, ). This is in agreement with preliminary studies conducted on the impact of NICE Evidence search (Rowley et al., ; Sbaffi et al., ). This finding is also supported by the responses provided regarding the main reasons for using NICE ES.…”
Section: Discussionsupporting
confidence: 92%
“…The present study is the first to report on the full scale implementation of the scheme and to include qualitative data from students undertaking the training sessions with champions. The results indicated that, consistently with previous evaluations conducted on the programme (Rees et al., ; Rowley et al., ; Sbaffi et al., ), there are objective advantages from participating to the NICE SCS. The most significant result of this study is the consistent improvement in search confidence that students experience after attending the peer taught training session.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations